Reducing HIV stigma and discrimination towards people living with HIV among healthcare workers at Primary Health Clinic - Faizah G, Nor; AR, Raudah; Nasirudin N, Mohd; Ahmad Fauzi, Fatimah; Zahrah MZ, Fatimah; I, Ismawati (Jurnal Ilmu Kesehatan, 2024)
Stigma and discrimination (S&D) towards people living with HIV (PLHIV) among healthcare workers (HCWs) in primary care are evidenced by discriminatory attitudes and perceived discrimination by PLHIV. Addressing this issue is crucial for improving patient adherence to treatment plans and achieving the goal of ending the AIDS epidemic by 2030. This project aims to determine the factors contributing to S&D towards PLHIV among HCWs in primary health care. The study consists of five phases, including four quantitative and one qualitative observation, conducted from September to December 2020. Two phases focused on staff training to measure knowledge, attitude, and practice (KAP), concluding with an in-depth interview. An audit of laboratory forms assessed labeling practices, and the ‘My Journey Survey’ identified areas associated with discrimination. Results showed that HCWs without training demonstrated more S&D. Paramedics and pharmacists had moderate to high knowledge scores, but their attitudes and practices were average. The bleeding room and pharmacy were identified as areas with acts of discrimination. Several interventions were implemented to improve HCW knowledge and practices, eliminate labeling practices, and enhance patient education and treatment literacy. Post-intervention surveys revealed significant improvements in most S&D domains among HCWs, with the achievable benefit not achieved (ABNA) gap closed from 19% to 0%. In conclusion, multi-pronged and consistent interventions are necessary to eliminate discrimination among HCWs towards PLHIV, focusing on increasing knowledge, changing work processes, and continuous promotion of awareness.